Gender and Justice: The Socio-Legal Implications Of Gender-Based Violence Legislation - Agus Haryanto; Rizky Wahyuni; Wulan Sari (International Journal of Sociology and Law, 2024)
This article examines the socio-legal impact of gender-based violence legislation on survivors and societal perceptions of justice. By evaluating the effectiveness of various legal protections and support systems for victims, the study assesses challenges such as enforcement, social stigma, and cultural attitudes. Findings suggest that while legal protections are essential, achieving gender justice requires broader social reforms to address deeply rooted biases and to empower survivors.